2009
DOI: 10.1186/1477-7525-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing quality of life in Moroccan postmenopausal women with osteoporotic vertebral fracture assessed by ECOS 16 questionnaire

Abstract: ObjectiveThe aim of the study was to evaluate factors influencing quality of life (QOL) in Moroccan postmenopausal women with osteoporotic vertebral fracture assessed by the Arabic version of ECOS 16 questionnaire.Methods357 postmenopausal women were included in this study. The participants underwent bone mineral density (BMD) measurements by DXA of the lumbar spine and the total hip as well as X-ray examination of the thoraco-lumbar spine to identify subclinical vertebral fractures. Patients were asked to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
7
17
0
1
Order By: Relevance
“…Highly educated women were also more likely to answer that they had good QOL; similar to the findings of other studies (Koundi et al, 2006;Abourazzak et al, 2009). All the domains showed that the higher the qualification, the higher the WHOQOL-BREF QOL scores.…”
Section: Discussionsupporting
confidence: 87%
“…Highly educated women were also more likely to answer that they had good QOL; similar to the findings of other studies (Koundi et al, 2006;Abourazzak et al, 2009). All the domains showed that the higher the qualification, the higher the WHOQOL-BREF QOL scores.…”
Section: Discussionsupporting
confidence: 87%
“…Through this analysis it was revealed, that higher education and to be an active worker affects QOL in a positive way. More highly educated women were also more likely to answer that they had good QOL; similarly to findings of other studies [38,165].…”
Section: Quality Of Lifesupporting
confidence: 85%
“…In Hungary the increasing of screening participation is desirable; the Hungarian National Mammography and Cytological Network aimed to improve the mammography and cervix screening rates by expanding the services of specialists, using ambulatory screening stations in the rural areas of Hungary [35]. Other type of diseases which may affect women's QOL -mainly in case of fracturesis osteoporosis [38][39][40][41][42]. In Hungary and also all over the world it is a type of noncommunicable diseases, which causes a great problem to health care systems through its prevalence and consequences (e.g.…”
Section: Regarding Malignant Tumors Breast Cancer Have Caused Women'mentioning
confidence: 99%
“…Gruplara Göre QUALEFFO anketi değerlendirmesi hastaların başvuru sebeplerinin vertebral kırığa bağlı şikayetlerden daha çok osteoporoz araştırılması amacıyla olması ve hastaların ağrı kesici kullanımının sorgulanmaması ağrı değerlendirmesini etkilemiş olabilir. Osteoporoz taraması amacıyla gelen postmenopozal kadınlarda yapılan benzer çalışmalarda da vertebral kırığı olanlarda olmayanlara göre yaşam kalitesinde bozulma bulunurken ağrı değerlendirmesinde anlamlı farklılık tespit edilmemiştir (17,18). Çalışmamızda vertebral kırığı olan osteoporotik kadınlarda mental fonksiyon osteopenik olanlara göre düşük seviyelerde bulundu.…”
Section: Discussionunclassified